Antibacterial Activity of Diethyl Ether Extract of Calocybe indica. - SHANKAR, S.; ANAND, R.; RAMESH, K. (Asian Journal of Chemistry, 2010)
The antimicrobial properties of diethyl ether extract of Calocybe indica was investigated against ten infectious bacterial strains. The extract of Calocybe indica showed better antibacterial activity against Ps. aeruginosa, Klebisella pneumoniae, Salmonella typhi, Streptococcus sp. using both disc diffusion and agar well methods.